Real-World Outcomes of Biologic Therapy for Juvenile Idiopathic Arthritis Associated Uveitis - Mano, Sofia Sousa (2019)
Purpose: We aim to report the outcomes and complications of patients with uveitis from Juvenile Idiopathic Arthritis (JIA) treated with biologic therapy. Materials and Methods: All patients who underwent treatment with biologic therapy for uveitis in the context of JIA between 2016 and 2017, followed in the Uveitis Department in Hospital de Santa Maria, were retrospectively included in the study.  Patient medical records were analyzed retrospectively and clinical outcome and complications were registered. Results: Nine patients (7 females, 2 males, 18 eyes) were included in the study. The mean age of JIA diagnosis was 6.6 years (±4,5) and the mean age of uveitis diagnosis was 7.9 years (±3,0). Six patients were being treated with adalimumab (ADA), 2 with Infliximab (IFX) and 1 with Tocilizumab (TCZ), and of them 8 (88,9%) were treated successfully for uveitis. The resolution of anterior chamber inflammation was obtained with a mean interval of 2 months for ADA and 3 months for IFX. Before starting biologic therapy 33,3% (n=3) patients were on oral steroids, 55,6% (n=5) were doing methotrexate and 11,1% (n=1) was doing cyclosporine. After biological treatment, no patient was on oral steroids. Regarding adverse effects, there are records of one reaction to infusion during the treatment with IFX and liver enzymes derangement with ADA, that resulted in the switch of therapy respectively to ADA and IFX. Conclusion: In this small cohort, ADA, IFX and TCZ showed to be effective and relatively safe for treatment of JIA-associated uveitis.